The Evaluation Of Leadership Role In Improving The Quality Of Education At Al Fida Qur'an Islamic Boarding School - Minallahi Ramadhan; Muhammad Azhar; Ahmad Baihaqi M; Edi Ahmad (Al-Khair Journal : Management, Education, and Law, 2023)
Abstract: Leadership has experienced difficult roles such as educators, managers, administrators, supervisors, and motivators in improving the quality of education, characterized by difficulties recruiting new students even schools are closed or schools disband. The purpose of this study is to evaluate the role of leadership in improving the quality of education in Pesantren Qur'an Al Fida. Using descriptive-qualitative methods, with a CIPP (Context, Input, Process and Product) model approach. Primary data sources obtained through direct observation in the field, and secondary data obtained through pesantren leadership report documents, representatives, teachers, and pesantren administration personnel through interviews, observations, and documentation. Data analysis using library research, by studying, collecting and processing data from various literature sources, both journals and books. The results of the study concluded that the evaluation of the role of leadership in improving the quality of education in the Qur'an Al-fia Islamic Boarding School. The contex stage has been carried out its leadership role. The input stage of pesantren leaders has a good influence, namely, providing life examples, paying attention, developing the potential of education staff and teachers, through education and training both seminars, workshops, webinars, providing motivation and a better vision and mission for the future. At the stage of the process, pesantren leaders make adjustments between programs that have been planned to improve the quality of education including improving teacher performance, involving students. The product stage, has implemented a teacher performance improvement program, comfortable learning for students, so that students excel both provincially and nationally. So it can be suggested that if you want to improve the quality of Qur'an Al Fida pesantren education, then increase the role of leadership.Keywords: Evaluation, Leadership Role, Quality of Education, Pesantren Qur'an Al Fida.